Growth Mechanism of Spiky Nb2O5 Nanoparticles and their Electrochemical Property. Issue 9 (1st July 2022) - Fuchigami, Teruaki; Yamamoto, Hayato; Tanibata, Naoto; Nakayama, Masanobu; Kakimoto, Ken-ichi
Abstract : Spiky nanoarchitecture composed of numerous nanorods and a spherical core has applications in various fields because of its high performance and durability. However, controlling the spiky structure is challenging because of an unclear formation mechanism. This study investigates the growth mechanism of spiky nanostructure by hydrothermally synthesizing Nb2 O5 with various conditions and additives, and it is shown that adsorption and gradual decomposition of ligands promote the formation of the spiky shape. Using oxalic acid as an additive and synthesizing at 160 °C, which is below oxalic acid's decomposition temperature, spherical Nb2 O5 with a rough surface that consists of a nanostructure with less than 5 nm size forms, and its surface is protected by oxalate ions. When the synthesis temperature increases to 180 °C, oxalate ions are decomposed, and nanorods grow on the spherical particles. The results show that oxalate ions suppress particle growth, promote self‐assembly, and control subsequent particle growth, resulting in complex nanostructures. When used as anode material in lithium‐ion batteries, the spiky Nb2 O5 nanoparticles show a higher capacity (143 mAh g −1 ) than collapsed spiky particles (92 mAh g −1 ) and nanorods (37 mAh g −1 ) because of fast lithium‐ion diffusion on the surface nanostructure and high dispersibility. Abstract : This study shows that suppression of particle growth and an assembly of nanoparticles are induced by binding of low molecular bridging ligands, and gradual decomposition of ligands causes subsequent particle growth, resulting in the formation of spiky nanostructures. In comparison with three kinds of nanoarchitectures, spiky Nb2 O5 shows higher dispersibility and capacity because of submicroscopic‐sized particles with nanoscale rods.